Why has Inequality in Germany not Risen Further After 2005? - Miriam Rehm; Kai Daniel Schmid; Dieter Wang (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
In this paper we explore the reasons for the trend reversal in the development of household market income inequality in Germany in the second half of the 2000s. We analyse to what extent the increasing relevance of capital income as well as the rising share of atypically employed persons have affected the development of income inequality over the last two decades. We use household data from the German Socio-Economic Panel from 1991-2011 and decompose market income into three income sources: (1) household labour income from full-time work, (2) household labour income from atypical work, and (3) household capital income. We apply the factor decomposition method suggested by Shorrocks (1982) to analyse the contribution of these income forms to overall inequality. Our results suggest that changes in the distribution of capital income were a key factor both in the strong increase of inequality in the first half of the 2000s and in the subsequent trend reversal. This finding contrasts with the reasoning that labour market developments were the main cause behind changes in inequality.
urn:nbn:de:101:1-201411242616
Keywords: D31; D33; 330; Market Income Inequality; Inequality Decomposition; SOEP